THE EFFECT OF REWARDS ON STUDENTS' RESPONSIBILITY IN LEARNING OF SCIENCE OBJECTS AND ITS OBSERVATIONS FOR CLASS VII OF JUNIOR HIGH SCHOOL - Malita Nisala Findy; Nur Kuswanti (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2022)
In learning science, students must be motivated to have several aspects of learning, including attitudes, so that in the future they can become human beings who have complete potentialis according to educational goals. The purpose of this study was to determine the effect of giving rewards on students’ responsibilities in Science Objects and Their Observations learning of class VII of junior high school. This research used a quasi-experimental design with a post test only control group design. The data were obtained through observations referring to the observation instrumens of students’ attitude.The population used were 320 students of class VII of SMP Negeri 2 Jombang and its samples were 64 students of two classes with 32 people each. The results of the study showed that there were differences of responsibility appearances between students of the experimental and the control classes. In the experimental class, the aspect of responsibility for carrying out the task got an average score of 7.25 and the control class got an average score of 6. For the aspect of responsibility of collecting assignment on time, the experimental class got an average score of 2 and the control class got an average score of 0.9. Their t test showed significant differences between them (p<0,05). Based on these results it can be concluded that reward influenced the students’ attitudes in learning Science Objects and Their Observation material of class VII of SMP Negeri 2 Jombang with higher occurrences in the class being given the reward treatment.